2003
DOI: 10.1046/j.1365-2443.2003.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin‐induced CXC chemokines, NAP‐2 and PF4, suppress polyploidization and proplatelet formation during megakaryocyte maturation

Abstract: Background : We previously reported that the express-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…25) In the present study, we observed that neutrophils surrounded MKs in BM (Fig. 5A) and strongly aggregated with MKs (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…25) In the present study, we observed that neutrophils surrounded MKs in BM (Fig. 5A) and strongly aggregated with MKs (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…18,38 We tested the effect of CXCL7 peptides (LDGF, ␤-TG, and NAP-2) on the in vitro production of megakaryocytes from CFU-Megs. In our studies, NAP-2 not only decreased megakaryocyte colony numbers but also reduced the number of cells per colony, confirming the reports that NAP-2 limits megakaryocyte growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, in this upregulated list (Supplementary Table S1) are secreted gene products such as Cxcl7, Cxcl4 and Thrombospondin 1. Cxcl7 and Cxcl4 block megakaryocyte development, 22 while Cxcl4 also supports the survival and chemosensitivity of hematopoietic cells. 23 Thrombospondin 1 promotes granulocytic 24 and blocks megakaryocyte differentiation.…”
Section: Identification Of Genes Altered By Aml1-eto9a In Microarraymentioning
confidence: 99%